Childhood anxiety disorders prevalence in Saudi Arabia - Alfakeh, Sulhi A. (Saudi Med J, 2021)
OBJECTIVES: To investigate the prevalence of childhood anxiety disorders in Saudi Arabia. METHODS: We conducted a cross-sectional study, between September and November 2019, in Saudi Arabia. The study group included the parents of 468 primary school children, aged 6-12 years. Parents completed the Screen for Child Anxiety Related Disorders (SCARED) screening instrument, translated to Arabic. The measured outcome was the prevalence of childhood anxiety disorders, determined from the scores on the SCARED instrument. RESULTS: Childhood anxiety disorders prevalence were as follows: 32.7% had one anxiety, 18.4% had 2, 10.9% had 3, 8.1% had 4, and 7.7% had 5. Of note, 22.2% of children did not have an anxiety disorder. CONCLUSION: Our results reveal a high prevalence of childhood anxiety disorders among primary school age children in Saudi Arabia. Based on these findings, conducting awareness campaigns and providing educational programs on childhood anxiety disorders might be important to improve the health outcomes of children.